PTH-033 A Systematic Approach to Standard Endoscopic Sampling of Bile Duct Strictures is Highly Accurate in the Diagnosis of Biliary Strictures. (4th June 2013) - Noorullah, O; Lekharaju, V P K; Wadsworth, C W; Brougham, K; Stern, N; Hood, S; Kaltsidis, C; Terlizzo, M; Sturgess, R
Abstract : Introduction: Accurate diagnosis of bile duct strictures as malignant or benign is imperative for optimal patient management, but is frequently difficult. Histological and cytological samples can be obtained at ERCP. Various techniques have been studied and reported specificities are generally very high. Sensitivities are modest and variable. The reported sensitivity is 33–57% for brush cytology and 43–81% for transpapillary histology. The yield may be increased by combining two sampling methods. Methods: Data was collected prospectively on all patients with bile duct strictures who underwent histology and cytology. Transpapillary, intraductal biopsies were obtained using a paediatric biopsy forceps (Boston Scientific, Radial Jaw 4, 2.0mm paediatric biopsy forceps, Hemel Hempstead, UK). Fluoroscopic guidance was used to selectively target the stricture. A minimum of 4 biopsies were obtained. Cytological samples were obtained using an over the wire brush (Boston Scientific, RX Biliary brush 2.1mm, Hemel Hempstead, UK). This involved multiple passes through the stricture and withdrawal of the brush in to the catheter after the final pass. On retrieval, the catheter was flushed with the cytology fixation fluid in to the cytology collection container and the brush was cut off and sent in the same container. The sample was delivered to the lab for processing to the lab immediately after the procedure. Patients diagnosed with benign strictures had a follow up with median length of 20 months (range 4–35). Results: 96 strictures were sampled using dual modality. 70 were malignant of which 49 were in the peri-hilar and proximal CBD and 21 in distal CBD. The sensitivity in diagnosis of malignant biliary strictures was 74% with an overall accuracy for all strictures of 81%. Histology was positive in 33/52 cases (63%) and cytology was positive in 29/52 cases (56%). Taken together, they yielded a significantly better result of 74%. The sensitivity was higher for peri-hilar (82%) as compared to distal strictures (57%). There were no false positives. No complications as direct result of either tissue acquisition techniques occurred. Conclusion: A highly systematic approach and combination of histology and cytology offers a significant advantage in diagnostic accuracy for both malignant and benign strictures. The high yield on cytology in our study may reflect attention to detail and prompt processing in the lab. None of the techniques adopted required specialised equipment or skills and could be adopted by any ERCP unit Disclosure of Interest: O. Noorullah: None Declared, V. Lekharaju: None Declared, C. W. Wadsworth: None Declared, K. Brougham: None Declared, N. Stern: None Declared, S. Hood: None Declared, C. Kaltsidis: None Declared, M. Terlizzo: None Declared, R. Sturgess Conflict with: Advisory board member and in receipt of honoraria from Olympus UK and Boston Scientific